PEMAKNAAN PESAN PADA UPACARA RITUAL TABOT (STUDI PADA SIMBOL-SIMBOL KEBUDAYAAN TABOT DI PROVINSI BENGKULU) - Linda Astuti (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
This study aimed to determine the stages in the Tabot ceremony, found out the meaning of the messages at each of these stages, and also looked for the symbols meaning in the ceremony. This research was expected to provide contributions to the development of Communication Sciences, particularly those related to the symbolic meaning of the message as well as verbal and nonverbal communication. This research used descriptive qualitative method. The results showed that the Tabot ceremony in Bengkulu was a hereditary tradition which carried out annually and was taken as an asset to the area. The ceremony was conducted by nine ritual, where each ritual laden with messages and meanings that carries meaning and tells a history or story. Keywords: the meaning of the message, culture symbols, tabot ceremony